Building Knowledge to Support Human Service Organizational and Management Practice: An Agenda to Address the Research-to-Practice Gap. (3rd April 2019) - McBeath, Bowen; Mosley, Jennifer; Hopkins, Karen; Guerrero, Erick; Austin, Michael; Tropman, John
Abstract: Leaders of human service organizations (HSOs) face significant pressures from policymakers and funders to justify practices and ensure successful outcomes, an issue that has implications for social work practitioners and evidence-informed management practice. Although empirical research has advanced understanding of the factors that improve human service effectiveness and organizational improvement, considerable research-to-practice gaps exist and the use and translation of knowledge into regular management practice remain limited. This article concerns how social work research can link human service organizational and management research to practice more robustly. Authors describe challenges that affect the ability of managers in HSOs to use research to inform practice. The analysis of these challenges supports a research capacity-building agenda focusing on (a) the identification and application of new methods of organization and management science, (b) the fostering of closer connections between researchers and practitioners, and (c) the provision of institutional and organizational resources for applied human services research. This macro-level agenda is designed to enhance practice-based research among schools of social work and leading HSOs, and also strengthen researcher–practitioner linkages, with the goal of promoting the advancement and utilization of research evidence in HSOs.